Učinkovitost uporabe ortoz za stopalo, vložkov in prilagojene obutve na fleksibilno plosko stopalo pri otrocih - Kacijan, Zala (Rehabilitacija (Ljubljana), 2019)
Background: Despite its prevalence, there are no clear clinical guidelines for conservative treatment of paediatric flexible flatfoot. We conducted a literature review to find evidence-based information about effectiveness of foot orthoses, shoe insoles or footwear for paediatric flexible flatfoot. Methods: The Pubmed bibliographic database was searched using various keywords related to paediatric flexible flatfoot and conservative treatment with foot orthoses, shoe insoles or footwear. Results: Eleven articles about effectiveness of foot orthoses, shoe insoles and footwear were included in the review according to the inclusion and exclusion criteria. Conclusions: The use of foot orthoses, shoe insoles and footwear modification has shown some positive effects and could be seen as a potential treatment method for children with flexible flatfeet. However, further good-quality research is needed to make recommendations for or against its use in clinical practice.
Keywords: Child; conservative treatment; Flatfoot; Foot Orthoses; konzervativno zdravljenje; medial longitudinal foot arch; medialni vzdolžni stopalni lok; plosko stopalo; rehabilitation